Practices of Care in Times of COVID-19 - Gómez Becerra, Marlene; Muneri-Wangari, Eunice (Frontiers in Human Dynamics, 2021)
We argue that the COVID-19 virus has been a trigger for emerging practices of care by being an actor with agency that transforms the everyday life of subjects by placing them under uncertainty. Therefore, this paper aims to show how practices of care emerged or were maintained as vulnerable groups were confronted by restrictions to movement and uncertainties following the outbreak of the COVID-19 pandemic. We demonstrate this using two case studies of the Maasai pastoral community in Narok, Kenya and the community kitchens in the city of Berlin, Germany. Thus, we seek to show how practices of care for, care about, and care with are carried out by the members of these communities during pandemic times. Granted that care remains highly contentious in feminist literature, this paper contributes to a growing body of literature on care in Feminist Political Ecology by broadening the conceptualization of care. The research builds on a typology of care relations based on practices of distribution, exchange, and reciprocity. This allows us to show when care is exercised in a unidirectional and hierarchical way and when in a multidirectional way reinforcing social bonds of responsibility and collective care that transcends the socio-nature boundaries.